Asteroseismic Diagram for Subgiants and Red Giants - Gai, Ning; Tang, Yanke; Yu, Peng; Dou, Xianghua (The Astrophysical journal, 2017)
Asteroseismology is a powerful tool for constraining stellar parameters. NASA's Kepler mission is providing individual eigenfrequencies for a huge number of stars, including thousands of red giants. Besides the frequencies of acoustic modes, an important breakthrough of the Kepler mission is the detection of nonradial gravity-dominated mixed-mode oscillations in red giants. Unlike pure acoustic modes, mixed modes probe deeply into the interior of stars, allowing the stellar core properties and evolution of stars to be derived. In this work, using the gravity-mode period spacing and the large frequency separation, we construct the Δ 1-Δ asteroseismic diagram from models of subgiants and red giants with various masses and metallicities. The relationship Δ 1-Δ is able to constrain the ages and masses of the subgiants. Meanwhile, for red giants with masses above 1.5 M , the Δ 1-Δ asteroseismic diagram can also work well to constrain the stellar age and mass. Additionally, we calculate the relative "isochrones" τ, which indicate similar evolution states especially for similar mass stars, on the Δ 1-Δ diagram.